Deciphering the Plasticizers for the Development of Polysaccharide based Biodegradable Edible Coatings - Lakhawat, Sudarshan S.; Sharma, Pushpender Kumar; Kumar, Sunil; Pandey, Aishwarya; Kumar, Vikram (Current Nutrition & Food Science, 2023)
There is persistently high demand for fresh fruits and vegetables all over the world. One of the crucial factors that reduce the shelf life of fruits and vegetables is temperature- dependent oxidation during transportation and long storage. Fruits and vegetable coating using ecofriendly coatings hold a great advantage over the other synthetic coating materials. The fruits and vegetables with coating can prevent rapid oxidation even at warm temperatures. They enhance the quality and shelf life and maintain nutritional properties. Though edible coatings prove to be beneficial, the major drawback associated with them is the vulnerability towards moisture- dependent rapid degradation of these fruits and vegetables. Use of appropriate plasticizers would be helpful in enhancing the moisture and oxidation resistance. The current review article will highlight the use of various plasticizers used with polysaccharide-based coatings.
Keywords: Plasticizers